HOUSE SALES INFORMATION SYSTEM IN BRANCH III UNIT PERUMNAS KARAWACI - Priyono Priyono; Aqwam Rosadi Kardian,S.kom.,MMSI (Jurnal Sistem Informasi, 1998)
In order to improve utilization of system processing sales information at branch III PERUMNAS Karawaci unit, then a system needs a good data handling and can provide information quickly. Efforts to address these needs with speed and accuracy is high. The speed of presentingÂ  the information will greatly assist in the leadership of the steps in making policies and decisions so that its impact will be promoting the company.